Factors Influencing Purchase Intention of the BYD Atto 1 Electric Car in Surabaya, Malang, and Sidoarjo - Decky Purhadi Suhendro Putro (Jurnal Indonesia Sosial Sains, 2026)
The development of electric vehicles (EVs) in Indonesia is accelerating rapidly, in line with the government's efforts to reduce carbon emissions and increase the use of clean energy. However, EV adoption still faces various challenges that affect consumers' purchase intention. This study aims to analyze the influence of mass media influence, environmental concern, government support, vehicle performance, price perception, and infrastructure on attitudes and subjective norms, and their impact on the purchase intention of the BYD Atto 1 electric vehicle, using the Theory of Planned Behavior (TPB) as the theoretical framework. This study employed a quantitative approach through a survey of prospective EV users, involving 120 respondents, with data analyzed using PLS-SEM. The results indicate that all proposed hypotheses yielded significant results, supporting the developed theoretical model. Therefore, this study provides an empirical understanding of how social, psychological, and structural factors shape attitudes and subjective norms, which ultimately influence purchase intention toward electric vehicles.